Pemanfaatan Augmented Reality untuk Pembelajaran Pengenalan Alat Musik Pianika (Informatics Department, Faculty of Mathematics and Natural Sciences, Udayana University, 2023)
People use technology as a learning medium to learn musical instruments such as guitar, drums, piano, and other musical instruments. Augmented Reality technology can be used to create an immersive experience for music students. AR unites two-dimensional and three-dimensional virtual objects into a real three- dimensional environment. In music theory, especially the basic theory of piano can actually be learned easily. Now many music learning methods are easy to obtain. However, most of them look boring and difficult to learn music for users. This has triggered the decline in public enthusiasm in learning various things about music. By applying Augmented Reality technology, boring methods can be minimized so that it becomes a more interesting and exciting learning method by using Augmented Reality technology that is able to provide an immersive experience for users.